2022
DOI: 10.1177/21568693221120066
|View full text |Cite
|
Sign up to set email alerts
|

The Risk for Food Insecurity and Suicide Ideation among Young Adults in the United States: The Mediating Roles of Perceived Stress and Social Isolation

Abstract: Young adults in the United States have the highest prevalence of suicidal thoughts of any adult age group. While limited, research indicates food insecurity heightens the risk of suicide ideation among young adults. However, research has not explored the pathways underlying the food insecurity—suicide ideation association among this population. Using 2008 data from Wave IV of the National Longitudinal Study of Adolescent to Adult Health (Add Health), we fill this gap by testing for the mediating roles of perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…26 Additionally, the analysis of 2008 data from Wave IV of the National Longitudinal Study of Adolescent to Adult Health revealed a significant association between FIS and suicidal ideation among young adults aged 24-32. 40 In the United States, the 2017 Youth Risk Behavior Survey involving high school students from 11 states also reported a link between FIS, suicidal behavior, and mental health. 27 The consistent findings from this study and prior research highlight the importance of addressing FIS as a potential risk factor for suicidal behaviors among university students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Additionally, the analysis of 2008 data from Wave IV of the National Longitudinal Study of Adolescent to Adult Health revealed a significant association between FIS and suicidal ideation among young adults aged 24-32. 40 In the United States, the 2017 Youth Risk Behavior Survey involving high school students from 11 states also reported a link between FIS, suicidal behavior, and mental health. 27 The consistent findings from this study and prior research highlight the importance of addressing FIS as a potential risk factor for suicidal behaviors among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies might play a crucial role in understanding the time-dependent nature of this relationship, shedding light on possible causeand-effect mechanisms, and pinpointing important factors that contribute to risk or provide protection. 22,40 Investigating the underlying factors that connect FIS to suicidal behaviors, including nutritional deficiencies, psychological distress, and coping strategies, can offer valuable insights for focused interventions. Furthermore, a more thorough analysis of the correlation between debt and mental health outcomes, including various forms of debt and financial burdens, could provide valuable and nuanced insights.…”
Section: Implications For Researchmentioning
confidence: 99%